The health of physiology: a perspective - O’Halloran, Ken D. (2016)
What does a health check for Physiology in the 21st century reveal? Has it run its course as a research discipline? Will it soon be confined to the lecture halls and libraries of contemporary institutions? Or on the contrary, does it have a bright future, a central role to play in the pursuit of fundamental knowledge for the benefit of human health? Physiology's current predicament is a paradox of sorts: increasingly invisible, and to some in rapid irreversible decline, yet it appears never as popular in terms of Society membership, and global celebrations of the discipline, which demonstrably go from strength to strength. As with any conundrum, there are elegant solutions, and a growing interest within the community to seek them out. Against the backdrop of significant failings of the modern reductionist approach, Physiology, with its holistic approach to integrative function of complex organisms, has never seemed so relevant and important. Yet there are worrying signs. Morale in many camps is low. Brand Physiology appears in poor shape to those pulling the purse strings; past its heyday, dated, maybe even dead! Many others at the centre and fringes of the discipline are optimistic for Physiology's future, but it is increasingly clear that physiologists must take action, not so as to merely protect Physiology per se, but critically, so as to ensure it is enabled to contribute to the delivery of ambitious expectations set by the wider community, notably funders spending public monies. Physiology is essential to the realisation of plans for better health outcomes. It is pivotal to progress, once one accepts that progress is a slow incremental affair. It is timely that many conversations have commenced with a view to charting a course for Physiology through troubled waters. I hope to add constructively to the debate with observations and discussion serving to nudge Physiology ever closer to centre stage, where she belongs, in the theatre of the life sciences.